203 An Evaluation of Polypharmacy and Adverse Drug Events in Older Adults with Rheumatic Disease. (16th September 2019) - Mooney, Niamh; Hannon, Evelyn; Buckley, Mary; Murphy, Grainne
Abstract: Background: Polypharmacy among older adults is a well-documented problem. The practice has been associated with potentially inappropriate medications (PIMs, adverse drug events (ADEs) and hospitalisation. This retrospective cohort study aims to evaluate polypharmacy, ADEs and anticholinergic burden in the ≥65 population with rheumatic disease. Methods: All patients who were ≥65 and had a diagnosed rheumatic disease were included in this study. Patients' medication lists, specific rheumatic disease, laboratory findings and associated comobidities were obtained from their medical charts at rheumatology outpatient clinics. The data was screened for PIMs using the Screening Tool of Older Persons' Medications (STOPP) criteria and probable ADEs using the WHO-UMC criteria. Anticholinergic burden was determined using the ACB calculator. Polypharmacy in this project was defined as ≥4 regular prescription medications. Results: 70 patients were studied. The prevalence of polypharmacy was 94%. The median (IQR) number of regular prescription medications was 7 (2-16). PIMs were recorded in 43 patients (61%). Increasing numbers of medications was a significant risk factor for PIMS (p=0.0027). ADEs were detected in 18 patients (26%). The ADE detection rate in PIM positive patients was 35% (15/43) and 11% (3/27) in PIM negative patients. A patient who was PIM positive had a statistically significant risk of having an ADE (p=0.047). Of the ADEs detected, 73% were due to a STOPP PIM. Increasing numbers of medications was a significant risk factor for an increased anticholinergic burden (p=0.017). An anticholinergic burden of ≥3 was a statistically significant risk factor for falls (p=0.025), however it was not a statistically significant risk factor for cognitive decline (p=0.073). Conclusion: There is a high prevalence of polypharmacy in older adults with rheumatic disease. Increasing numbers of medications is statistically associated with increased number of PIMs, ADEs and increased anticholinergic burden.